Protein profiling of SH-SY5Y neuroblastoma cells: The effect of rhein - Cockova, Zuzana; Ujcikova, Hana; Telensky, Petr; Novotny, Jiri (Journal of biosciences, 2019)
4,5-Dihydroxyanthraquinone-2-carboxylic acid (Rhein) has been shown to have various physiological and pharmacological properties including anticancer activity and modulatory effects on bioenergetics. In this study, we explored the impact of rhein on protein profiling of undifferentiated (UC) and differentiated (DC) SH-SY5Y cells. Besides that, the cellular morphology and expression of differentiation markers were investigated to determine the effect of rhein on retinoic acidinduced neuronal cell differentiation. Using two-dimensional gel electrophoresis and matrix-assisted laser desorption/ ionization-time-of-flight mass spectrometry we evaluated the changes in the proteome of both UC and DC SH-SY5Y cells after 24 h treatment with rhein. Validation of selected differentially expressed proteins and the assessment of neuronal differentiation markers were performed by western blotting. Proteomic analysis revealed significant changes in the abundance of 15 proteins linked to specific cellular processes such as cytoskeleton structure and regulation, mitochondrial function, energy metabolism, protein synthesis and neuronal plasticity. We also observed that the addition of rhein to the cultured cells during differentiation resulted in a significantly reduced neurite outgrowth and decreased expression of neuronal markers. These results indicate that rhein may strongly interfere with the differentiation process of SH-SY5Y neuroblastoma cells and is capable of inducing marked proteomic changes in these cells.
Keywords: Gene Expression Regulation, Neoplastic; Cell Line, Tumor; regulace genové exprese u nádorů; buněčná diferenciace; Neuronal Outgrowth; neuronální růst; neurony; Neuroblastoma; neurity; proteomika; Neurites; Anthraquinones; lidé; Neural Stem Cells; Humans; Neurons; anthrachinony; nervové kmenové buňky; Proteomics; nádorové buněčné linie; neuroblastom; Cell Differentiation